Usos/significados da Etnomatemática mobilizados na formação inicial de professores de matemática no Instituto Federal de Roraima – IFRR - Ghedin, Leila Marcia (2018)
Since 1988, the training process of Math teachers Ethnomatematics in its curricula, both as a subject and as a study object. This insertion usually brings the discussion about a dual ethnomathematical and academic mathematical relationship. In this work, we intend to clarify this duality by looking at the uses/meanings of ethnomathematics both in the literature and in the context of the initial education that establishes it in the curriculum, considering the Wittgensteinian view of mathematics, as language games in language activity. In this way, our research question consists of understanding how mathematics graduates of the course offered by the Federal Institute of Vocational, Scientific and Tecnological Eduation of Roraima (IFRR), mobilize uses/meanings of ethnomathematics, in their context of training. Our investigative path adopts a methodical attitude inspired by the philosophical therapy of Wittgenstein and the deconstruction of Derrida. In order to understanding of the graduates significations, we searched for the uses/significations of the ethnomathematics, in the research corpus, constituted by different language/cultural practices such as: the literature, the documentation set of Roraima’s public HEI Math courses, their completion of course works, field observations of the pedagogical practices of the ethnomathematics discipline and the impressions of the students of the degree course in Mathematics of IFRR, signified by means of an open questionnaire. The enlightenment/analysis exercise was done through some narratives of the therapeutic path of meanings, or through fictional dialogic staging whose characters perform their speeches in the traces of the ethnomathematical meanings of the research corpus. In the path of the therapy, through the corpus, it was possible to clarify that the established visions of ethnomathematics are linked to the mathematics uses/adjectives. The therapeutic deconstruction of these uses points to another form of use of mathematics, and, hence, of signified ethnomathematics, according to Wittgenstein, as cultural practices/language games that grammatically normalize human actions in order to unequivocally achieve the purposes of the activities that mobilize these games.